A preliminary analysis of microRNA as potential clinical biomarker for schizophrenia. Issue 3 (5th February 2015) - Sun, Xin‐yang; Zhang, Jin; Niu, Wei; Guo, Wei; Song, Hong‐tao; Li, Heng‐yu; Fan, Hui‐min; Zhao, Lin; Zhong, Ai‐fang; Dai, Yun‐hua; Guo, Zhong‐min; Zhang, Li‐yi; et al.
Abstract : MicroRNAs (miRNA, miR) have been implicated as promising blood‐based biomarkers for schizophrenia patients. This study aimed to clinically validate miRNA as potential schizophrenia biomarkers. Plasma levels of 10 miRNAs were analyzed using qPCR in a cohort of 61 schizophrenia patients and 62 normal controls, as well as 25 patients particularly selected for a six‐week antipsychotic treatment course. Positive And Negative Syndrome Scale (PANSS), Global Assessment Scale (GAS) and Clinical Global Impression (CGI) were administered to assess the clinical symptoms. The results demonstrated that a panel of miRNAs consisting of miR‐30e, miR‐181b, miR‐34a, miR‐346 and miR‐7 had significantly increased expression levels with significant combined diagnostic value (AUC:0.713; sensitivity:35.5%; specificity:90.2%). In response to pharmacological treatment, expression levels of miR‐132, miR‐181b, miR‐432 and miR‐30e were significantly decreased. In addition, the improvement of clinical symptomatology was significantly correlated with the changes of miR‐132, miR‐181b, miR‐212 and miR‐30e expression levels. Furthermore, the decreases of plasma levels of miR‐132 and miR‐432 were significantly greater in high‐effect subgroup than those in low‐effect subgroup after six‐week treatment course. We conclude that miR‐30e, miR‐181b, miR‐34a, miR‐346 and miR‐7 combined as a panel are potentially useful non‐invasive biomarkers for schizophrenia diagnosis. Markers miR‐132, miR‐181b, miR‐30e and miR‐432 are potential indicators for symptomatology improvements, treatment responses and prognosis for schizophrenia patients. © 2015 Wiley Periodicals, Inc.